2016
DOI: 10.1051/parasite/2016001
|View full text |Cite
|
Sign up to set email alerts
|

Refractory hypoglycaemia in a dog infected withTrypanosoma congolense

Abstract: A 20 kg German shepherd dog was presented to a French veterinary teaching hospital for seizures and hyperthermia. The dog had returned 1 month previously from a six-month stay in Senegal and sub-Saharan Africa. Biochemistry and haematology showed severe hypoglycaemia (0.12 g/L), anaemia and thrombocytopenia. Despite administration of large amounts of glucose (30 mL of 30% glucose IV and 10 mL of 70% sucrose by gavage tube hourly), 26 consecutive blood glucose measurements were below 0.25 g/L (except one). Rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
(31 reference statements)
1
13
1
Order By: Relevance
“…The only evidence of the life-cycle of Lepotrema is supplied by Kondo et al ( 2016 ), who described metacercariae of L. clavatum from three cnidarians, the moon jellyfish Aurelia aurita (Linnaeus) ( s.l . ), the Japanese sea nettle Chrysaora pacifica (Goette) and the ghost jellyfish Cyanea nozakii Kishinouye, from the Seto Inland Sea, Japan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only evidence of the life-cycle of Lepotrema is supplied by Kondo et al ( 2016 ), who described metacercariae of L. clavatum from three cnidarians, the moon jellyfish Aurelia aurita (Linnaeus) ( s.l . ), the Japanese sea nettle Chrysaora pacifica (Goette) and the ghost jellyfish Cyanea nozakii Kishinouye, from the Seto Inland Sea, Japan.…”
Section: Resultsmentioning
confidence: 99%
“…This host distribution can best be considered in the context of the recent report that metacercariae of Lepotrema clavatum infect medusae of several cnidarian species in Japanese waters (Kondo et al, 2016 ). These authors further demonstrated that Thamnaconus modestus and Psenopsis anomala , which both live in association with jellyfish as juveniles, had both nematocysts and juvenile L. clavatum in their guts.…”
Section: Discussionmentioning
confidence: 99%
“…Other sensitive animals express less severe clinical forms. Consequently, CAT clinical diagnosis remains difficult [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The causative agents are mainly Trypanosoma congolense , Trypanosoma vivax and Trypanosoma evansi [ 2 , 5 ]. Dogs are also susceptible to infection [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation